The Best Inoculation Technique Applied on Gyrinops versteegii Tree Trunk - Wahyuni, Resti; Prihantini, Amalia Indah (Biosaintifika: Journal of Biology & Biology Education, 2020)
Agarwood is a non-timber forest product having high economic value, however, its population in nature is getting decrease. Gyrinops versteegii, an agarwood-producing plant, has been listed in Appendix II CITES, therefore, exploitation of the agarwood in nature must be reduced. An effort to reduce the agarwood exploitation the nature is by agarwood cultivation including cultivation of agarwood-producing plant and agarwood inoculation. Some of agarwood inoculation methods are simpori and implant techniques. Simpori is a modified inoculation method using porous nail and Fusarium solani, meanwhile implant technique uses drill and pieces of wood that is soaked in F. solani spores. The present study aimed to determine the best inoculation technique applied to G. versteegii tree trunk at 4 to 5m height, comparing simpori and implant techniques. This study used completely randomizes design with two treatments (simpori and implant techniques). The result showed that the averages yield of production agarwood produced by simpori and implant techniques are 0.66 and 0.64%, respectively. Based on SNI 7631:2011, the visual quality of the produced agarwood belongs to kemedangan TG.C. In conclusion, both simpori and implant technique produced agarwood in similar quality and quantity at six months inoculation, however, simpori is more practical for application in the field. This study provides additional data about agarwood produced by simpori and implant technique and give the alternative methods for agarwood farmers producing their agarwood themselves.